Susceptibility for Some Infectious Diseases in Patients With Diabetes: The Key Role of Glycemia - Chávez-Reyes, Jesús; Escárcega-González, Carlos E.; Chavira-Suárez, Erika; León-Buitimea, Angel; Vázquez-León, Priscila; Morones-Ramírez, José R.; Villalón, Carlos M.; Quintanar-Stephano, Andrés; Marichal-Cancino, Bruno A. (Frontiers in Public Health, 2021)
Uncontrolled diabetes results in several metabolic alterations including hyperglycemia. Indeed, several preclinical and clinical studies have suggested that this condition may induce susceptibility and the development of more aggressive infectious diseases, especially those caused by some bacteria (including Chlamydophila pneumoniae, Haemophilus influenzae and Streptococcus pneumoniae, among others) and viruses [such as coronavirus 2 (CoV2), Influenza A virus, Hepatitis B, etc.]. Although the precise mechanisms that link glycemia to the exacerbated infections remain elusive, hyperglycemia is known to induce a wide array of changes in the immune system activity, including alterations in: (i) the microenvironment of immune cells (e.g., pH, blood viscosity and other biochemical parameters); (ii) the supply of energy to infectious bacteria; (iii) the inflammatory response; and (iv) oxidative stress as a result of bacterial proliferative metabolism. Consistent with this evidence, some bacterial infections are typical (and/or have a worse prognosis) in patients with hypercaloric diets and a stressful lifestyle (conditions that promote hyperglycemic episodes). On this basis, the present review is particularly focused on: (i) the role of diabetes in the development of some bacterial and viral infections by analyzing preclinical and clinical findings; (ii) discussing the possible mechanisms by which hyperglycemia may increase the susceptibility for developing infections; and (iii) further understanding the impact of hyperglycemia on the immune system.